ANALISIS POLIFARMASI SERTA HUBUNGAN POTENSI INTERAKSI OBAT TERHADAP GLUKOSA PASIEN GERIATRI - Dewi, Hasna; Agustiansyah, Lukidita; Dian Andini (Politeknik Tiara Bunda, 2025)
Diabetes mellitus is achronic metabolic disease that requires long-term treatment. Elderly people with multimorbidity often use multiple medications, known as polypharmacy, which can increase the risk of drug interactions. This study aims to analyze polypharmacy prescriptions and determine the relationship between drug interactions and blood glucose levels in geriatric patients with type2 diabetes. This study is non-experimental with a descriptive-analytical design through a retrospective cross-sectional approach. Sampling used random sampling in the form of medical records of171 geriatric patients with type 2 diabetes. Using univariate and bivariate analysis in the form of chi-square statistical tests with a significance level of<0.05. The results showed that the incidence of type 2 diabetes in geriatric women was higher than in men at119 (69.59%), with the largest distribution of geriatric patients in the 60-69 year age range (77.77%). Based on polypharmacy prescriptions, the most common type of polypharmacy encountered was minor polypharmacy (5-9 drugs)(95.3%), and 159 patients (92.98%) had the potential for interactions. Based on the mechanism pattern, pharmacodynamic interactions occurred in413 cases (74.95%), with the most common level of interaction severity being moderate, occurring in340 cases (61.7%). Chi-square test results showed a relationship between potential drug interactions and blood glucose levels, with p-value of 0.000<0.005.